2018
DOI: 10.1101/387043
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

EGFR confers exquisite specificity of Wnt9a-Fzd9b signaling in hematopoietic stem cell development

Abstract: SummaryThe mechanisms of Wnt-Frizzled (Fzd) signaling selectivity and their biological implications remain unclear. We demonstrate for the first time that the epidermal growth factor receptor (EGFR) is required as a co-factor for Wnt signaling. Using genetic studies in zebrafish, paired with in vitro cell biology and biochemistry, we have determined that Fzd9b signals specifically with Wnt9a in vivo and in vitro to elicit β-catenin dependent Wnt signals that regulate hematopoietic stem and progenitor cell (HSP… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(5 citation statements)
references
References 189 publications
(214 reference statements)
0
5
0
Order By: Relevance
“…We confirmed secretion of F7-Ab, F7, L6, and F7L6 from CHO cells by SDS-PAGE and Coomassie Blue staining and immunoblotting ( Figure 1B). Using a dot blot with lysates of HEK293T cells carrying loss of function mutations in FZD1, 2 and 7 (F127-KO) (Voloshanenko et al, 2017) or in LRP6 (LRP6-KO) (Grainger et al, 2019) confirmed binding specificity of each of these molecules. FZD7-specific binders (F7 and F7L6) only reacted with lysates upon FZD7 overexpression (note that endogenous FZD7 expression in LRP6 KO is below the level of detection), whereas LRP6 specific binders (L6 and F7L6) only reacted with lysates of cells expressing LRP6 ( Figure 1C).…”
Section: Design Specificity and Expression Of F7l6mentioning
confidence: 88%
See 4 more Smart Citations
“…We confirmed secretion of F7-Ab, F7, L6, and F7L6 from CHO cells by SDS-PAGE and Coomassie Blue staining and immunoblotting ( Figure 1B). Using a dot blot with lysates of HEK293T cells carrying loss of function mutations in FZD1, 2 and 7 (F127-KO) (Voloshanenko et al, 2017) or in LRP6 (LRP6-KO) (Grainger et al, 2019) confirmed binding specificity of each of these molecules. FZD7-specific binders (F7 and F7L6) only reacted with lysates upon FZD7 overexpression (note that endogenous FZD7 expression in LRP6 KO is below the level of detection), whereas LRP6 specific binders (L6 and F7L6) only reacted with lysates of cells expressing LRP6 ( Figure 1C).…”
Section: Design Specificity and Expression Of F7l6mentioning
confidence: 88%
“…For example, Reck, a glycosylphosphatidylinositol-anchored cell surface protein, acts together with Gpr124, a 7transmembrane protein, to promote Wnt7a-Fzd-Lrp5/6 signaling to promote angiogenesis in the developing central nervous system (Cho et al, 2017;Cho et al, 2019;Eubelen et al, 2018;Vallon et al, 2018). Furthermore, we recently identified a novel function for Egfr in mediating Wnt9a-Fzd9-Lrp5/6 signaling during hematopoietic development in zebrafish (Grainger et al, 2019). The use of engineered proteins capable of engaging specific WNT receptors, such as F7L6, may overcome the need for the recruitment of specificity-conferring co-receptors, such as Reck, Gpr124 and Egfr, and thus replace the need for purification of biologically active WNT proteins.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations